2015
DOI: 10.1007/s12149-015-0987-1
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of iterative reconstruction parameters with 3-dimensional resolution recovery, scatter and attenuation correction in 123I-FP-CIT SPECT

Abstract: We determined that the optimal reconstruction parameter for OSEM(RRSCAC) was 90 update numbers with 6.6 mm FWHM of the Gaussian filter. Our results suggested that the optimal reconstruction parameters have a potential to improve the performance and the image quality of (123)I-FP-CIT SPECT in comparison with the FBP reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 16 publications
0
16
0
3
Order By: Relevance
“…The present study showed that the SBRs calculated by images without ACSC reconstruction were lower than those calculated by images reconstructed with CTACSC, CTAC, or Chang AC, which is in accordance with the results of the previous studies. [ 8 – 11 ] Matsutomo et al [ 8 ] reported that the quality of the SPECT images reconstructed by OSEM with CTACSC was superior to that reconstructed by filtered back projection (FBP) with Chang AC, and the diagnostic ability of DSND by the former appeared to be superior to the latter even though the difference was not statistically significant. Lange et al [ 10 ] compared the effect of OSEM with CTAC, Chang AC, and no AC on the SBRs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study showed that the SBRs calculated by images without ACSC reconstruction were lower than those calculated by images reconstructed with CTACSC, CTAC, or Chang AC, which is in accordance with the results of the previous studies. [ 8 – 11 ] Matsutomo et al [ 8 ] reported that the quality of the SPECT images reconstructed by OSEM with CTACSC was superior to that reconstructed by filtered back projection (FBP) with Chang AC, and the diagnostic ability of DSND by the former appeared to be superior to the latter even though the difference was not statistically significant. Lange et al [ 10 ] compared the effect of OSEM with CTAC, Chang AC, and no AC on the SBRs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, with recent increasing availability of hybrid SPECT/computed tomography (CT) scanners, several studies have compared a conventional uniform AC method like Chang with a nonuniform AC method like CT attenuation correction (CTAC). [ 8 – 11 ] Although the phantom data indicated that CTAC improved recovery of the tracer accumulation in the striata, increased the SBR, and enhanced the image quality of I-123 FP-CIT SPECT, [ 8 , 9 ] the utility of these corrections in clinical practice is still under debate. [ 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…Next, the six sealed pieces in the columnar part were filled with 123 I aqueous solutions of 80, 40, 20, 10, and 5 kBq/mL, 19,20 as well as one with only water. The surrounding volume was sealed with a 2.5 kBq/mL 123 I aqueous solution as the background.…”
Section: Equipment/methodsmentioning
confidence: 99%
“…The radioactivity concentration of the background was set to 5.56 or 7.44 kBq/mL. The simulation settings were based on the imaging guidelines of DaT-SPECT and a previous study [15][16][17]. The main energy window was 143-175 keV (159 keV ± 20%).…”
Section: Simulation Code and Phantommentioning
confidence: 99%